Asset Diversification and Pension Fund Performance in the West African Economy: Asymmetric Evidence from Nigeria - Adedeji Daniel Gbadebo; Abiola Olaide Ayodele; Emmanuel Imuede Oyasor (The Indonesian Journal of Accounting Research, 2026)
This study aims to investigate the asymmetric effects of pension fund asset allocation on the return on investment (ROI) of pension fund administrators in Nigeria using the Nonlinear Autoregressive Distributed Lag (NARDL) framework. Employing monthly data spanning 2007 to 2023, the analysis examines the roles of federal government securities, equities, corporate bonds, money market instruments, mortgage funds, and real estate assets in shaping pension fund performance. The findings reveal that while government securities remain the dominant investment vehicle, their long-term returns are constrained by inflationary pressures and interest rate volatility. Diversification into equities, corporate bonds, and real estate contributes positively to ROI, though the effects are modest and statistically weak in both the short and long run. Importantly, the symmetry tests indicate that increases and decreases in asset allocation do not yield significantly different outcomes, suggesting that diversification strategies remain effective regardless of market direction. Policy implications point to the need for regulatory reforms that gradually liberalize asset allocation guidelines, encourage market deepening, and promote innovative portfolio management practices. The study concludes that a balanced approach between safety and diversification is critical for enhancing pension fund performance, safeguarding retiree welfare, and supporting Nigeria’s broader developmental agenda.